Indonesian Students’ Acquisition of English Address Terms: A Case Study in a University in the United Kingdom - KOMILIE SITUMORANG (Indonesian Research Journal in Education |IRJE|, 2018)
This study explored on how the transfer of Indonesian Address Terms (ATs) influenced the production of English ATs and in what ways Indonesian students accommodated the acquisition of the English ATs during the study abroad. This study focused on the five participants who were recruited through the purposive sampling. Designed to capture the participants’ experiences, this study employed a qualitative case study approach. The written discourse completion test and semi-structured interviews were employed to look at the pragmatic transfer and the acquisition of the address terms. The findings indicated that students’ home cultures of showing politeness by addressing people through contextual variables were challenged under the local cultures which view the equality and casual direct addressing as politeness. Participants were also found to show salient efforts to accommodate the English ATs in multifaceted ways. These efforts shed light to the teaching of English ATs in classroom. Implications to teaching English ATs in classroom in Indonesia are also discussed.